2007
DOI: 10.1024/0300-9831.77.6.359
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C, Vitamin B12, Folate and the Risk of Osteoporotic Fractures. A Case-Control Study

Abstract: Water-soluble vitamins influence the development of an adequate structure of bone tissue, but there is scant information relating them with osteoporotic fractures. We analyze whether serum vitamin C, vitamin B12, and erythrocyte folate, or dietary intake of vitamin C and folate, are related with osteoporotic fractures in the elderly. A hospital-based case-control study was carried out at the Hospital of Jaén (167 cases, 167 controls), Spain. Cases were defined as patients aged 65 or more years with a low-energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…Three of these defined a case based on fracture (hip (26,34) or any fragility fracture (35) and measured blood levels of AA. Falch, et.…”
Section: Epidemiology and Human Studies In Vitamin Cmentioning
confidence: 99%
“…Three of these defined a case based on fracture (hip (26,34) or any fragility fracture (35) and measured blood levels of AA. Falch, et.…”
Section: Epidemiology and Human Studies In Vitamin Cmentioning
confidence: 99%
“…Blood vitamin C was inversely correlated with fracture risk in elderly adults 69,70 and was significantly lower in elderly osteoporotic females 29 . some studies found that low vitamin C status in smokers significantly increased the risk of hip fracture, particularly where vitamin e intake was low 66,71 , although others have found no association 72 .…”
Section: Calcificationmentioning
confidence: 98%
“…Results from three observational studies have indicated that significant associations with bone health 361 were surprisingly stronger for moderate rather than higher vitamin C intakes (6,79,81) . For example,…”
mentioning
confidence: 99%
“…for the second quartile (79) or for the third quartile (6,81) of vitamin C intake rather than the highest intake 364 levels. Similar cross-sectional observations have been reported for associations with serum vitamin…”
mentioning
confidence: 99%
See 1 more Smart Citation